PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KOMPETENSI KEAHLIAN KONSTRUKSI BANGUNAN GEDUNG PADA MATERI TEKNIK PENGUKURAN TANAH - Maryam Ruhul Aflah (Pondok Pesantren Baitul Qur`an Sambas, 2024)
As time goes by, education becomes important and necessary to produce a generation that is superior and capable in skills. In particular, development in vocational education continues to be carried out in order to produce high quality human resources. This research aims to describe a literature review regarding the application of Problem Based Learning (PBL) in land measurement techniques in vocational schools. This learning model aims to improve students' critical thinking skills in land measurement engineering material. The research method used is descriptive analysis with a literature review approach by reviewing and concluding articles from journals and books. The use of Problem Based Learning (PBL) in learning is considered to be able to help students to solve problems that exist in the real world later.